1978
DOI: 10.1111/j.1432-1033.1978.tb12772.x
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Purification and Properties of Cathepsin‐E‐Like Acid Proteinase from Rat Spleen

Abstract: A unique acid proteinase different from cathepsin D was purified from rat spleen by a method involving precipitation at pH 3.5, affinity chromatography on pepstatin -Sepharose 4B and concanavalin A -Sepharose 4B, chromatography on Sephadex G-100 and DEAE-Sephacel, and isoelectric focusing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…After electrophoresis at 4OC, the gels were incubated at low pH and the proteolytic activity was visualized by Coomassie blue staining. The two bands obtained are typical for the two forms of cathepsin E (Yamamoto et al, 1978; Kageyama and Takahashi, 1980). This fraction 23 which contained the higher amount of cathepsin E was used for subsequent digestions with the peptide library GAX,,AG, the native protein gp96 or the substrate melittin.…”
Section: Methodsmentioning
confidence: 99%
“…After electrophoresis at 4OC, the gels were incubated at low pH and the proteolytic activity was visualized by Coomassie blue staining. The two bands obtained are typical for the two forms of cathepsin E (Yamamoto et al, 1978; Kageyama and Takahashi, 1980). This fraction 23 which contained the higher amount of cathepsin E was used for subsequent digestions with the peptide library GAX,,AG, the native protein gp96 or the substrate melittin.…”
Section: Methodsmentioning
confidence: 99%
“…The final phases of purification are affinity chromatography on agarose bound to pepstatin or to an antibody against cathepsin E [2]. A homogenous preparation of mature cathepsin E has been obtained from human gastric mucus [4], human erythrocytes [33] and rat spleen [34], neutrophiles [35] and epidermis [36]. Cathepsin E preparations are kept at -20°C, in buffer with pH 7.0 containing 50% glycerol.…”
Section: Purificationmentioning
confidence: 99%
“…Recently several workers have isolated cathepsin D by affinity chromatography using suitable ligands such as substrate [8] and inhibitors [12,21,22]. In the previous work we have shown that rat spleen possesses two types of acid proteinases strongly inhibited by pepstatin [23,24]. One of these was isolated in a pure form by the use of affinity chromatography on pepstatinSepharose 4B and concanavalin-A -Sepharose 4B, and identified as a cathepsin-E-like enzyme that differs from cathepsin D [24].…”
mentioning
confidence: 99%